DIFFERENCE OF VITAMIN C CONTENT IN PICKLED MANGO FRUIT - Sri Palupi (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2003)
his research is a survey one which aims at knowing the content of vitamin C of salted mangoes and knowing existances or non-extances of the content of vitamin C of salted mangoes in Jogjakarta Special Region (DIY). Knowing existances or nonextances of the differences of the content of vitamin C of salted mangoes the supply of vitamin C will -be known so that the need of vitamin C for someone can be considered as references. The samples are salted mangoes sold at Mirota Kampus, Gardena and Ramai shop. These shops only sell them every sample was analyzed to find out its water and vitamin C contents using